Współczesne problemy filozofii religii - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2015)
This article contains two complementary parts. In the first part I attempt to answer a general question what was and what is conditioned formulating and solving problems on the grounds of the philosophy of religion. I give also an account of the most important (in my opinion) problems which should be today solved by this philosophy. In the second part of my remarks I present contemporary examples of combining philosophy with a certain challenge. It is not a new issue; nevertheless it fits into new contexts of modern philosophical and religious arguments, concerning polemics taken from the Catholic and Protestant point of views to be precise, within the Enlightenment and post-Enlightenment philosophical tradition. The opposition highlighted above is being represented in this tradition by both Alasdair MacIntyre and Allan Bloom.
Keywords: filozofia religii